Gene Duplication and Protein Evolution in Tick-Host Interactions - Mans, Ben J.; Featherston, Jonathan; de Castro, Minique H.; Pienaar, Ronel (Frontiers in Cellular and Infection Microbiology, 2017)
Ticks modulate their hosts’ defense responses by secreting a biopharmacopiea of hundreds to thousands of proteins and bioactive chemicals into the feeding site (tick-host interface). These molecules and their functions evolved over millions of years as ticks adapted to blood-feeding, tick lineages diverged and host-shifts occurred. The evolution of new proteins with new functions are mainly dependent on gene duplication events. Central questions around this are the rates of gene duplication, when they occurred and how new function evolve after gene duplication. The current review investigate these questions in the light of tick biology and considers the possibilities of ancient genome duplication, lineage specific expansion events and the role that positive selection played in the evolution of tick protein function. It contrasts current views in tick biology regarding adaptive evolution with the more general view that neutral evolution may account for the majority of biological innovations observed in ticks.